Translating "hyperdivercity" for the Museum (interview with Nicole van Dijk) - Carvalho, Ana (2017)
The Museum Rotterdam has changed from a tra- ditional historical museum (founded in 1905 as the Museum of Antiquities) into the city museum of Rotterdam, featuring interaction and participation as the backbone of its work, where stories about contemporary and historical heritage are being told and shared. The museum reopened in 2016 at a new venue in the centre of Rotterdam, choosing the contemporary transnational city and its diver- sity to be the main focus of its strategies.